2020
DOI: 10.3390/su12177045
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Sustainability Challenges of the Food-Delivery Sector: Finding from the Deliveroo Italy Case Study

Abstract: The food delivery sector is assuming increasing importance in the distribution of food products and meals as it is becoming an ordinary component of consumption habits. However, the growth of the sector has inevitably affected the demand for freight transport, especially in urban areas. The aim of this study was to investigate the main enabling factors affecting the adoption of sustainable strategies, among which the electro-mobility, in the food delivery sector and what obstacles to dissemination can be seen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 50 publications
0
15
0
2
Order By: Relevance
“…In recent years, the pandemic COVID-19 has changed the business operation landscape, which highly depends on online transaction (Alaimo et al , 2020; Galati et al , 2020; Chang and Meyerhoefer, 2020; Troise et al , 2021), and Internet usage has increased rapidly. The trend of using online transaction can be traced for the past several years, and the Internet World Statistic reported that there are 4.574 million Internet subscribers worldwide reported in the year 2019, representing 58.7% of the world's total population and expected to grow year after year (Internet World Statistic, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the pandemic COVID-19 has changed the business operation landscape, which highly depends on online transaction (Alaimo et al , 2020; Galati et al , 2020; Chang and Meyerhoefer, 2020; Troise et al , 2021), and Internet usage has increased rapidly. The trend of using online transaction can be traced for the past several years, and the Internet World Statistic reported that there are 4.574 million Internet subscribers worldwide reported in the year 2019, representing 58.7% of the world's total population and expected to grow year after year (Internet World Statistic, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of these climate changes has serious biophysical effects specifically, on the agriculture sector by the decrease in crop productivity, invasions of pathogens and pests, shifts in crop planting dates, and reduced resilience of agroecosystems. On the other hand, the agriculture sector and different land-use practices are responsible for emitting anthropogenic greenhouse gases (GHGs) and carbon (CO 2 ) emissions [1][2][3]. It is observed that climate change has a larger impact in developing countries than in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Some FDAs, slightly and highly searched during the pandemic, seem not to exist only one year before (respectively, Foodracers and Glovo). Under a qualitative perspective, the sample of FDAs have been analyzed through official websites, reports (Pierre and Michaud, 2020;Just Eat, 2019;, literature (Caratù, 2018;Privitera, 2019;Galati, et al, 2020) and market data (Statista, 2020) with regard to companies' information, characteristics of the offer to consumers and background/opportunities before and during the Covid-19 pandemic. As a common result, according to Just Eat (2020), it emerges a general growth trend for the entire Italian food delivery market, which nowadays represents between 20-25% of the entire home delivery service (18% in 2019).…”
Section: Results and Main Findingsmentioning
confidence: 99%
“…Such growth has been recorded not only in large cities, but also in peripheral areas and provinces. Galati et al, 2020;Glovo, 2020;Uber Investor, 2020 It emerges from Italian facts that one of FDAs weaknesses is the distribution (capillarity) of the partner restaurants/couriers in the Italian country. Indeed, FDAs are mainly available in urban areas (e.g., Just Eat has reached over 900 cities, while Deliveroo barely exceeds 200 cities), therefore leading to an unequal distribution on the territory (Privitera, 2019).…”
Section: Results and Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation